Beyond morphology: cryptic diversity in 9 new Gyrodactylus species (Monogenea: Gyrodactylidae) associated with northwest African barbels (Cyprinidae) and remarks on Gyrodactylus nyingiae Shigoley, Rahmouni, Louizi, Pariselle and Vanhove, 2023 - Chahrazed Rahmouni; Mária Seifertová; Andrea Šimková (Parasitology)
Cryptic diversity, characterized by morphologically similar but genetically distinct species, poses significant challenges to traditional taxonomic methods. Within monogeneans parasitizing northwest African barbels, this complexity hampers species identification, limiting our understanding of diversity, distribution and evolutionary relationships. Supported by previously published genetic data, we morphologically delineate herein 9 Gyrodactylus species from Morocco. Newly described species include G. agnesei sp. nov. and G. benhoussai sp. nov. from Luciobarbus rabatensis, with the latter also found on Carasobarbus fritschii, and both G. deburonae sp. nov. and G. marruecosi sp. nov. from L. massaensis. Additionally, G. diakini sp. nov. and G. louiziae sp. nov. were identified from L. rifensis and L. yahyaouii, respectively. Pterocapoeta maroccana harboured G. pterocapoetai sp. nov., morphologically resembling G. shigoleyae sp. nov. from sympatric L. zayanensis. We also examined taxonomical discrepancies between Gyrodactylus species from L. ksibi and L. pallaryi, evaluated the status of previously described G. nyingiae and described G. qninbai sp. nov. from L. ksibi. Our findings highlight the conservative morphology in northwest African Gyrodactylus, characterized by an ancestral median ridge in the ventral bar membrane, similar to that found in species from Eurasia. Subtle phenotypic features, like bifurcations in dorsal bars and proportions of marginal hooks, serve as diagnostic traits. We further evidenced a potential host-switching event from northwest African to Iberian hosts, correlating with the region’s geological history and cyprinid dispersal events during intermittent closures of the Strait of Gibraltar. These insights illuminate the complex evolutionary processes driving gyrodactylid diversification in the West Mediterranean.